Pengembangan Sistem Manajemen Permintaan Pelayanan dan Aduan Karyawan (Studi Kasus: Fakultas Ekonomi dan Bisnis Universitas Brawijaya) - Reynald Daffa Pahlevi; Faizatul Amalia; Arief Andy Soebroto (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Providing the best service is a priority for the Faculty of Economics and Business Universitas Brawijaya (FEB UB) to give a comfortable and safe impression. If there are services provided that are not in accordance with the services that should be provided, both lecturers, educational staff and FEB UB guests can submit complaints through Whatsapp social media which is managed by the operator and admin. After the complaint is received by the operator or admin, the complaint is filtered according to the complaint category and then forwarded to the Whatsapp group according to the complaint category. This process has a flow that is quite complicated and takes a long time. Besides that, the submitted complaints are not kept by FEB UB, where complaints can be used as evaluation materials in each semester to improve better service. From the existing problems, a system development was carried out to manage service requests and employee complaints. The development of this system uses the Prototyping method. The process in system development starts from the stage of literature study, needs analysis, design, implementation, and testing. The results of the needs analysis were carried out in 2 iterations at the prototyping stage, there were 7 actors, 35 functional needs, and 1 non-functional requirement. The system was developed using the Javascript programming language using the Express.js framework and Bootstrap. Testing uses unit testing and integration with 100% results for all tested test cases and testing using validation testing with 100% pass results. While testing compatibility, the functionality contained in the system can be run on all browsers but still has some issues with the appearance and performance of the system.